Formulasi Bakso Nabati Tepung Kacang Merah dan Jamur Tiram Putih terhadap Sifat Kimia dan Sensoris - Netti Herawati; Priscila Manuella Gultom; Emma Riftyan (Universitas Djuanda, 2024)
Vegetable meatballs are products made from vegetable protein but similar to the properties of real meat. The purpose of this study was to obtain selected formulation of vegetable meatballs from red bean flour and oyster mushrooms to chemical and sensory qualities according to SNI 3818−2014 concerning combination meat balls. The researched method used a complete randomized design (RAL) with four treatments and four repetition so that 16 experimental units were obtained. The results showed that the ratio of red bean flour and oyster mushrooms had a significant influence on moisture content, ash, fat, protein, crude fiber, as well as on descriptive and hedonic sensory assessments such as color, aroma, taste, elasticity, and overall acceptance. Based on this study, the selected treatment was KJ2 treatment and has met SNI 3818−2014. KJ2 treatment has a water content of 58.07%, ash content of 1.88%, fat content of 0.49%, protein content of 8.67%, crude fiber content of 3.41%. Panelist liked the overall sensory assessment of KJ2, which had a slightly brown color, smell of red bean flour and white oyster mushrooms, tasted red bean flour and white oyster mushrooms, and chewy.